PERANCANGAN WEBSITE PEMESANAN MAKANAN BERBASIS QR CODE DENGAN METODE WATERFALL - Anugerah Syear Yasyub Samuel Tadu; Rabbanie Aulia Althaaf (Journal of Information Systems and Business Technology, 2025)
The development of digital technology has driven transformation in various aspects of business services, including the culinary industry. To improve operational efficiency and customer convenience, a modern and integrated ordering system is needed. This study discusses the design of a QR Code-based food ordering website using the waterfall software development method. This system allows customers to make orders independently through personal devices without the need to download additional applications. The website is designed using the PHP programming language and MySQL database, with QR Code as a direct access media to the digital menu page. The implementation results show that this system is able to speed up the ordering process, reduce queues, and minimize recording errors. Thus, this system can be an effective solution for culinary business actors in improving service quality and operational efficiency.